(untitled) (American Journal of Islam and Society, 2012)
It is becoming increasingly apparent that the Muslim world is undergoing a political upheaval of historic proportions. The Arab Spring is one of the most recent and dramatic manifestations, with millions of men and women across the Arab world taking to the streets – often in the face of brutal repression ‒ to demand the reform or overthrow of their authoritarian governments. Their bravery has already led to the ouster of four dictators – in Tunisia, Egypt, Libya, and Yemen – and the process is still far from over. But this uprising is only part of a much broader phenomenon, as a review of just the past five years demonstrates. In late 2008, largely free and fair elections ended two years of military-backed emergency rule in Bangladesh, and put the country back on a democratic track. In 2009, similar elections in Indonesia consolidated the democratic regime that had been in place there for just over a decade. That same year in Iran, by contrast, national elections, which were widely viewed as having been rigged, led to the so-called “Green Revolution” – the biggest prodemocratic uprising against the authoritarian regime there since the revolution of 1979. In 2010, Iraq held its second, and far more representative, elections since the overthrow of the Ba’athist regime. In 2011, national elections in Turkey that returned the AK Party to power with its largest electoral victory yet, coupled with ongoing judicial investigations into subversive activities by hard-line authoritarian elements, marked a decisive turning point in Turkey’s democratic evolution. In 2012, the willingness of Senegal’s president to step down peacefully after losing an election there seemed to confirm the victory of democracy in that country as well. As the suppression of Iran’s Green Revolution, the 2012 military coup that interrupted Mali’s democratic experiment, and the ongoing violence in several of the other transitioning polities, indicate the process is neither smooth nor unidirectional. Several aspects of the current upheaval, however, are already clear. First and foremost, the political mobilization of the Muslim masses – the eruption of “people power” – is now an irreversible reality for the foreseeable future, so that only regimes that are genuinely representative and accountable can hope to enjoy any legitimacy in the future. Second, as public opinion poll after poll has demonstrated, democracy has become a hegemonic concept throughout the Muslim world as well ‒ meaning that effective governance and opposition will need to take place within its institutional and normative parameters. Third, as Table 1shows, judging by the most recent election results, in most of the Middle Eastern states at least, political parties rooted in an Islamist background are likely to garner the lion’s share of electoral support for some time to come ...